THE EFFECTIVENESS OF PARTNER READING STRATEGY IN READING TEACHING: PERSPECTIVES FROM STUDENTS AND TEACHERS AT MTs SWASTA AL-FALAH CIKAUM - Dea Guchi Putri Gunawan; Dody Wahyudi Purnama; Jufrianto Sibarani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to examine the effectiveness of the partner reading strategy in improving students’ reading skills and to explore students’ and teachers’ perceptions of its implementation in classroom practice. The study is grounded in the issue of students’ low reading proficiency and limited engagement in reading activities, which are often dominated by conventional teaching approaches. A mixed-methods approach was employed, combining a quasi-experimental design using a pretest–posttest format with qualitative data collected through questionnaires, observations, and interviews. The participants consisted of 30 seventh-grade students and several teachers at MTsS Al Falah Cikaum. The findings revealed a significant improvement in students’ reading performance, as indicated by the increase in mean scores from pretest to posttest. In addition, both students and teachers responded positively to the implementation of the partner reading strategy, particularly in enhancing engagement, interaction, and learning motivation. However, several challenges were identified, including unequal participation and differences in students’ reading abilities. It can be concluded that the partner reading strategy is effective in improving students’ reading skills when implemented in a structured manner and supported by appropriate teacher facilitation. ABSTRAK Penelitian ini bertujuan untuk mengkaji efektivitas strategi partner reading dalam meningkatkan kemampuan membaca siswa serta mengeksplorasi persepsi siswa dan guru terhadap implementasinya dalam pembelajaran. Latar belakang penelitian ini didasarkan pada rendahnya kemampuan membaca siswa serta kurangnya keterlibatan aktif dalam kegiatan membaca di kelas yang masih didominasi oleh pendekatan konvensional. Penelitian ini menggunakan pendekatan mixed-methods dengan desain kuasi-eksperimen melalui pretest-posttest, serta didukung oleh data kualitatif yang diperoleh melalui angket, observasi, dan wawancara. Subjek penelitian terdiri dari 30 siswa kelas VII dan beberapa guru di MTsS Al Falah Cikaum. Hasil penelitian menunjukkan adanya peningkatan signifikan pada kemampuan membaca siswa setelah penerapan strategi partner reading, yang ditunjukkan oleh peningkatan skor rata-rata dari pretest ke posttest. Selain itu, siswa dan guru memberikan respons yang cenderung positif terhadap strategi ini, khususnya dalam meningkatkan keterlibatan, interaksi, dan motivasi belajar. Meskipun demikian, beberapa kendala seperti ketidakseimbangan partisipasi dan perbedaan kemampuan siswa masih ditemukan. Dengan demikian, dapat disimpulkan bahwa strategi partner reading efektif dalam meningkatkan kemampuan membaca siswa apabila diimplementasikan secara terstruktur dan didukung oleh fasilitasi guru yang optimal.